Greening the logistics operations in the agri-food sector: What do sustainability reports disclose - Kontopanou Maria; Mouzakitis Yannis; Tsoulfas Giannis T. (E3S Web of Conferences)
The agri-food complex constitutes a critical sector in the discourse of sustainable transitions, with the corresponding stakeholders covering the primary, secondary, and tertiary sectors. Similarly, supply chain management is a complex process for any type of organisation or product, with a significant contribution to its environmental footprint. This paper focuses on linking the aforementioned areas, aiming to present a structured and comprehensive mapping of practices (application or use of methods, tools, and procedures) which improve the environmental performance of the corresponding supply chain(s). A number of thirty sustainability reports of companies active in all stages of the agri- food system in the Greek market are analysed, and the conclusions discuss the intensity, the diversity, the outcomes, the popularity and the quality of published information of green logistics, in the light of five specific operations: management of transportation, storage, materials planning, packaging, and management of third-party logistics services providers.